ANALISIS PENGARUH PERILAKU ORGANISASI PEMERINTAHAN DAN STRES KERJA TERHADAP SEMANGAT KERJA ASN PADA DINAS PENDIDIKAN KABUPATEN INDRAGIRI HILIR - Sari Harto Dirgantoro; Agus Maulana; Sri Hidayanti (Indragiri Research Center (ingreat), 2026)
This study was conducted to analyze the extent to which government organizational behavior and work stress affect the work spirit of ASN in the Indragiri Hilir Regency Education Office, with the TPP gap phenomenon as a contextual background. Using a methodology using a quantitative approach because it aims to test the relationship between variables through statistical analysis and numerical measurements. The population in this study were all ASN employees at the Indragiri Hilir Regency Education Office. Based on organizational data, the number of ASN employees in the Indragiri Hilir Education Office is around 41 people (consisting of structural officials, general functional, and technical personnel and PPPK). The analysis tool used smart pls. The results of this study are that organizational behavior has a positive and significant influence on ASN work spirit. This is evidenced by the original sample value of 0.646, a beta coefficient of 6.856, and a p value <0.05. and work stress has a negative and significant effect on ASN work spirit, with an original sample value of -0.338, a beta coefficient of 3.073, and a p value <0.05.